Bank non-performing loans cyclical analysis and econometric modelling for economic activity in 1999-2013 - Yong Chacón, Marlon (2016)
We looked for the effect of the fundamental macroeconomic variables (interest rates, exchange rate, production and price level) on the magnitude of bank non-performing loans in Costa Rica, for the period of January 1999 to November 2013. We did a cyclical analysis with the Hodrick-Prescott Filter and econometric modelling with Panel Data, on non-performing loans for its term and economic activity for the entire National Financial System, public and private banks, because they have the bigger proportion of credit given in the nation. The economic activities chosen were: i) agriculture, ii) commerce, iii) construction, iv) consumption, v) industry, vi) services; in the fact that this activities represent the biggest proportion of the credit given to the private sector. There was evidence of a differentiated behavior of non-performing loans depending of its term, time horizon and economic activity, even in its aggregation in the entire System, public and private banks.